The Realization of Assertive and Directive Speech Acts in Apple’s Instagram Captions - Nanda Alifia; Widhiyanto; Bahri, Saeful (LPPM Universitas Advent Indonesia, 2025)
This research aims to analyze assertive and directive speech acts in “Apple” official account captions on Instagram using Searle’s theory related to environmental topics, particularly those promoting nature. With the increasing role of social media in corporate communication, companies like Apple have leveraged platforms such as Instagram to engage with their audience and raise awareness of important environmental. By examining the language used in Apple's captions, this study aims to explore how the company employs various communication strategies to influence public attitudes and encourage positive behavior toward environmental sustainability. Through a descriptive qualitative approach, 56 speech acts from the 44 captions were analyzed. The most frequently used speech act by Apple’s captions on Instagram is assertive acts, which are used 50 times and they are asserting (38%), stating (28%), informing (22%), describing (8%), claiming and giving opinion (2%) then directive acts only 6 times. It is utilized to inform, motivate, and provoke thought among followers. From the whole result, this research highlights the role of social media in shaping consumer perceptions and fostering environmental responsibility. The findings provide valuable insights into the effectiveness of language as a tool for building trust and ongoing communication to drive environmental action Keywords: Instagram, pragmatic, speech act